Flame-retardant properties and mechanism of LGF/PBT/DOPO-HQ-conjugated flame-retardant composites - Sun, Junzhuo; Zhang, Daohai; Shang, Xiaoyu; Tan, Fang; Bao, Dongmei; Qin, Shuhao (Frontiers in Chemistry, 2022)
The 10-(2,5-dihydroxy phenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-HQ) was used as a conjugated flame retardant, long fiber reinforced polybutylene terephthalate (LGF/PBT/DOPO-HQ) conjugated flame retardant composites were prepared in this paper. The combustion properties of LGF/PBT/DOPO-HQ conjugated flame retardant composites were studied. The results showed that with the addition of 14% DOPO-HQ, the conjugated flame retardant composites achieve a V-0 ranking and LOI is 26.4%, moreover, the average heat release rate (Av-HRR), peak heat release rate (PHRR), total heat release (THR) of the conjugated flame retardant composites decreased. This behavior showed the DOPO-HQ exhibits superior flame retardant on LGF/PBT/DOPO-HQ conjugated flame retardant composites. In addition, with the addition of DOPO-HQ to LGF/PBT composites, LGF/PBT/DOPO-HQ conjugated flame retardant composites released the containing phosphorus compounds in the gas phase and produced the polyphosphate that can contribute to the formation of residual char in condensed phase during their burning, which improves the flame retardant properties of LGF/PBT/DOPO-HQ conjugated flame retardant composites. These behaviors showed that the DOPO-HQ acted in both the gas phase and condensed phase to achieve the effective flame retardant performance for LGF/PBT/DOPO-HQ conjugated flame retardant composites.